Laparoscopic management of acute cholecystitis with hepatic choristoma of the gall bladder wall: case reportand review of the literature - Espitia, Francisco Terrazas; Davila, David Molina; de Alba, Carlos Armando Diaz (International Surgery Journal, 2019)
Choristoma is a term which refers to the presence of histologically normal tissue in a heterotopic location; hepatic choristoma is a condition in which hepatic tissue can be found in abnormal locations above or below the diaphragm, the gallbladder wall being the most frequent heterotopic site for implantation, this disease is usually asymptomatic and is rarely detected preoperatively with imaging studies due to a general lack of knowledge of this entity. We present the case of a 37 year old male patient who presented with acute abdominal pain in the right upper quadrant, colicky in nature, accompanied by nausea and vomiting; a HIDA 99 mTc scan revealed gallbladder diskynesia as well as a radiolucent bilobulated image. Upon laparoscopy, we encountered two masses on the superoanterior gallbladder wall and Hartmann´s pouch, which upon histopathological specimen examination revealed the presence of hepatic choristoma. This entity should be considered whenever a soft tissue mass is reported on the anterior gallbladder wall on imaging studies; It has been reported that hepatic choristoma is at higher risk for development of hepatocellular carcinoma and should be removed en bloc with the gallbladder.